1992
DOI: 10.1002/j.1873-5924.1992.tb00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the Tokyo Spot Foreign Exchange Market Consistent With the Efficient Market Hypothesis?

Abstract: Recent Studies in the area of foreign exchange market efficiency have employed time series analysis to test for the absence of long‐run equilibrium or cointegration relationships among the exchange rates for the major currencies. Cointegration directly violates the weak form of the Efficient Market Hypothesis in a speculative efficient market (Granger, 1986). In this study, we address the efficiency of the Tokyo spot foreign exchange market while updating the test procedures developed by Phillips and Ouliaris … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Like Sephton and Larsen, they argue that asset prices may be cointegrated due to model misspecification, and Lajaunie and Naka (1997) find cointegration to be sensitive to the sample period. Rush (1989, 1991), Lajaunie, Mcmanis, and Naka (1996), Lajaunie and Naka (1992), and Coleman (1990) do not find any cointegration and thus conclude that markets are weak form efficient, a conclusion contradicted by Wu and Chen (1998).…”
Section: Foreign Exchange Market Efficiencymentioning
confidence: 70%
“…Like Sephton and Larsen, they argue that asset prices may be cointegrated due to model misspecification, and Lajaunie and Naka (1997) find cointegration to be sensitive to the sample period. Rush (1989, 1991), Lajaunie, Mcmanis, and Naka (1996), Lajaunie and Naka (1992), and Coleman (1990) do not find any cointegration and thus conclude that markets are weak form efficient, a conclusion contradicted by Wu and Chen (1998).…”
Section: Foreign Exchange Market Efficiencymentioning
confidence: 70%
“…Baillie and Bollerslev (1989), however, find common stochastic trends in a sample of seven exchange rates, whereas, contrary to the two other authors, they apply the multivariate Johansen procedure. Coleman (1990), Copeland (1991), Tronzano (1992), Lajaunie and Naka (1992), Diebold, Gardeazábal, and Yilmaz (1994), Lajaunie, Naka, and McManis (1996), and Rapp and Sharma (1999) cannot detect cointegration of exchange rates for periods up to the end of the 1990s. On contrary, Alexander and Johnson (1992), Masih and Masih (1994) and Crowder (1994) can find long-run relationships among exchange rates on a US dollar basis and Karfakis and Parikh (1994) on the basis of the Australian dollar.…”
Section: Introductionmentioning
confidence: 86%
“…Among other econometric techniques, a cointegration analysis has been employed by several recent studies to examine foreign exchange market efficiency. The majority of prior empirical work (e.g., Coleman, 1990;Copeland, 1991;Lajaunie, McManis, & Naka, 1996;Lajaunie & Naka, 1992;MacDonald & Taylor, 1989;Rapp & Sharma, 1999) has found that spot exchange rates for various major currencies generally are not cointegrated during the modern float. The absence of cointegration and thus a cointegrating vector and the error correction model (ECM) (e.g., Engle & Granger, 1987) implies that the current value of one currency cannot be predicted by past values of other currencies.…”
Section: Introductionmentioning
confidence: 99%